Copepoda and Cladocera fauna of TMI 12 Pond (Elazig) - Saler, Serap; Arslan, Serkan (Ege Univ, 2007)
Copepoda and Cladocera fauna of TMI 12 Pond located near by Hazar Lake (Elazig) were investigated between November 2005 - October 2006. 2 species of Copepoda and 5 species of Cladocera were identified. Cyclops vicinus was dominant species from Copepoda, where as Ceriodaphnia reticulata from Cladocera was found to be the most observed species.
Keywords: Hazar Lake; Copepoda; Cladocera; seasonal variation; TMI 12 Pond